Tumor necrosis factor/cachectin-induced intravascular fibrin formation in meth A fibrosarcomas (The Rockefeller University Press, 1988)
Recent studies have indicated that TNF can promote activation of the coagulation mechanism by modulating coagulant properties of endothelial cells. In this report, we demonstrate that infusion of low concentrations of TNF (3 micrograms/animal) into mice bearing meth A fibrosarcomas leads to localized fibrin deposition with formation of occlusive intravascular thrombi in close association with the endothelial cell surface. Studies with 125I-fibrinogen showed tenfold enhanced accumulation of radioactivity in tumor within 2 h after TNF infusion. Western blots of tumor extracts subjected to SDS-PAGE and visualized with a fibrin-specific mAb indicated that fibrin forms in the tumor after the TNF infusion. Electron microscopic studies demonstrated fibrin strands, based on the characteristic 21-nm periodicity, which appeared to be adherent to the endothelial cell surface. Further ultrastructural studies indicated that fibrin formation, first evident within 30 min of the TNF infusion, led to occlusive thrombi limited to the tumor vascular bed (i.e., not in the normal mouse vasculature) within 2 h and was associated with an 80% reduction in tumor perfusion based on studies with Evans blue. In view of previous work concerning TNF induction of endothelial cell procoagulant activity, the hypothesis that tumor cell products prime the response of endothelium to this cytokine was tested. Supernatants of cultured meth A fibrosarcomas obtained serum-free conditions, which had no intrinsic procoagulant activity, considerably enhanced tissue factor induction in endothelium in response to submaximal concentrations of TNF. The factor(s) in the tumor-conditioned medium appeared to be distinct from IL-1, fibroblast growth factor, IFN-gamma, TNF, endotoxin, TGF-alpha, and TGF-beta. These studies delineate a novel model of localized clot formation in which thrombosis is initiated by a pathophysiologic mediator, TNF, and provides an opportunity to examine mechanisms in the microenvironment directing clot formation to the tumor vascular bed.